Strengthening Natural Tourism Empowerment Construction through Brand Strategy - Based Online Marketplace - WIDYASTUTY, Anak Agung Sagung Alit; WIDIANA, Muslichah Erma (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
This study aimed to focus on strengthening the construction of natural tourism empowerment through a brand strategy-based online marketplace. The analytical tool in this study was A’WOT analysis, which is a combination of AHP analysis and SWOT analysis. Data collection methods were through observation, documentation, and interviews with stakeholders, including representatives of the Bangkalan Regency Tourism and Culture Office, Situbondo Regency Tourism and Culture Office, and two tourism industry observers. The results showed that if all programs are implemented and executed by referring to the legal basis set by the government, then the strengthening of natural tourism empowerment construction through a brand strategy-based online marketplace can be achieved and can improve the economic development in a community, especially in Bangkalan Regency. The strengthening of its construction is by managing the website through the online promotion of tourism products, improving facilities and infrastructure to support tourism activities, optimizing additional service facilities at tourist destinations, and optimizing the management of tourism objects.